Impact of ICT based extension services on dairy production and household welfare: The case of iCow service in Kenya - Marwa, M.E.; Mburu, John; Rao, E.J.O.; Okeyo Mwai, Ally; Kahumbu Stephanou, Su (Canadian Center of Science and Education, 2020)
Smallholder dairy farmers have the challenges of accessing timely and reliable agricultural information, and this limits them from realizing maximum farm output. The use of information and communication technologies (ICT) as a farming extension tool by smallholder farmers has the potential to reverse the scenario and improve farmers’ outputs and incomes leading to increased welfare. This study employed the Propensity score Matching approach to evaluate the impacts of ICT-based extension services, in this case, iCow services on milk production, milk income, and household income using cross-sectional data from a survey of dairy farmers in Uasin Gishu, Nyandarua and Bomet counties of Kenya. The use of ICT-based iCow services is shown to increase Annual milk production per cow, milk income, and household income by 13%, 29%, and 22%, respectively. Partnerships between network providers and research institutes should be encouraged as part of bridging the extension gap occasioned by reduced public expenditure on extension services.